MiR-1248: a new prognostic biomarker able to identify supratentorial hemispheric pediatric low-grade gliomas patients associated with progression - Catanzaro, Giuseppina; Besharat, Zein Mersini; Carai, Andrea; Jäger, Natalie; Splendiani, Elena; Colin, Carole; Po, Agnese; Chiacchiarini, Martina; Citarella, Anna; Gianno, Francesca; Cacchione, Antonella; Miele, Evelina; et al. (Biomarker Research, 2022)
Pediatric low-grade gliomas (pLGGs), particularly incompletely resected supratentorial tumours, can undergo progression after surgery. However to date, there are no predictive biomarkers for progression. Here, we aimed to identify pLGG-specific microRNA signatures and evaluate their value as a prognostic tool.
Gesehen am 26.08.2022